Physico-chemical Modification of the Fibrous Filter Nozzles for Purification Processes of Water and Air; IOP Conference Series: Materials Science and Engineering; Vol. 168 : Radiation-Thermal Effects and Processes in Inorganic Materials (RTEP2016) - Bordunov S. V.; Galtseva (Gal’tseva) O. V. Olga Valerievna; Natalinova N. M. Nataliya Mikhailovna; Rogachev A. A.; Ruizhi Zhang (Technologies and equipment for their implementation, 2017)
Title screen